OBAMAS REMARKS ON TRAYVON MARTINS DEATH SEEN FROM CDA VIEWPOINTS: AN EXAMPLE OF AUTHENTIC ACADEMIC WRITING MATERIAL - Listyani, Listyani (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2018)
Racism and all its problems like injustice, inequality, discrimination, and so on, have become an interestingly never-ending topic to be discussed along the history. Even in America, a country which is so rich with its fighters of racial discrimination and injustice, this problem still occurs here and there. No matter how hard these heroes speak up their voices, this problem remains unsolved, or, at least, not entirely solved. One event, for example, happened on February 26, 2012in Sanford, Florida, the United States of America. The victim was a young man named Trayvon Martin; an Afro-American high school student. George Zimmerman shot this seventeen-year-old teenager, which led to death. Zimmerman was a 28-year-old Hispanic American man. At that time, he worked as a watchman coordinator in the neighborhood. Martin temporarily stayed there. Obama, who was then the President of the United States, made a speech on Martins death. This paper analyzes Barack Obamas speech from Discourse Analysis viewpoints, as well as the ideological and cultural discourse contained in the speech. In the text analysis, some significant aspects are discussed based on my understanding of SFL (Systemic Functional Linguistics), that is, the aspects of connections, like mode, tenor, and field. Another central issue to be discussed in this paper is the ideological and cultural aspects of Obamas remarks upon Trayvon Martins death. This speech can be a very good example of how an argumentative writing appeals so many people and makes them sympathize with the victim of the shooting. Through this paper, I hope that my own understanding of discourse analysis will be deepened, and readers will also gain some new horizon and knowledge of discourse study in general, including the cultural and ideological analysis of the text under study. I also hope that more convincing speeches of the authentic world like this one can benefit students of Academic Writing.